Establishment of geographical information technology to be used as the aid for plant ecology study in Carey Island, West Malaysia - Redzwan, G; R, Saraswathy; M.Z., Rozainah (Malaysian Journal of Science, 2010)
This study was carried out to establish a technological means of mapping the location of plant in the West Malaysia ecosystem with a simple approach with geographical information tools covering 10 000 m2. Conventionally, the mapping of plant uses perpendicular grid lines as X-Y axis according to the distance from the point of origin (Xo and Yo). This technique was found to be challenging especially at the heavily shrub areas. Acquiring the perpendicular grid lines connecting the X-Y axis was replaced with the use of hand-held global positioning system (GPS). It used the World Geodetic System 1984 (WGS 84). Coordinates information from GPS was uploaded into Geography Information System (GIS). The tools in geographical information technology (GIT) have enabled the plot for X-Y axis gridlines to be redrawn with GIS instead of using the ordinary graph technique. Statistical comparison with the analysis of regression has shown that the use of GIT could replace the conventional technique for the mapping of plants ecosystem. Statistical comparison between conventional and GIT, using correlation coefficient for both X axis and Y axis have given values of R2= 0.97 and 0.99, respectively. Therefore, tools in GIT were found to be suitable for the used of plant mapping in West Malaysia.